THEORETICAL FOUNDATIONS OF TEACHING CHILDREN TO MONOLOGICAL SPEECH - Rimbayeva Ozoda Bazarbayevna (International Journal of Business, Law and Political Science, 2024)
this article provides a number of information and feedback on the theoretical foundations of teaching children to monological speech and on monological speech